Nitrogen Exsolution and Bubble Formation in Titan's Lakes. Issue 23 (3rd December 2019) - Farnsworth, Kendra K.; Chevrier, Vincent F.; Steckloff, Jordan K.; Laxton, Dustin; Singh, Sandeep; Soto, Alejandro; Soderblom, Jason M.
Abstract: Titan's surface liquids are composed primarily of methane, ethane, and dissolved atmospheric nitrogen. The nitrogen content depends on the alkane composition and temperature, and exsolves as bubbles when these parameters are sufficiently perturbed. Herein, we present an experimental study of nitrogen bubbles in methane–ethane liquids, and propose that both methane and ethane are required for bubbles to form under Titan conditions. Bubbles occur when methane composes 40–95 mol% of the alkanes within the liquid. We identify two mechanisms that produce bubbles: ethane mediated titration and temperature‐induced stratification. Both of these mechanisms produce a metastable nitrogen supersaturation within the liquid; equilibration triggers rapid nitrogen exsolution in the form of bubbles. Such equilibration could cause bubble events in Titan's lakes, possibly explaining the transient "Magic Island" features seen by Cassini RADAR (bubbles within the liquid column), and the presence of deltas in Ontario Lacus. Plain Language Summary: Saturn's largest moon, Titan, has stable lakes on its surface composed of liquid methane, ethane, and dissolved atmospheric nitrogen. While nitrogen can dissolve into the liquid (dissolution), it can also be forced out of the liquid (exsolution). Nitrogen bubbles in Titan's lakes have been hypothesized, but not experimentally measured under Titan surface conditions. Here we create bubbles in a laboratory under Titan conditions using two methods: ethane slowly added to methane (titration) and temperature‐induced methane‐ethane liquid layering (cooling then warming). Both mechanisms create a metastable supersaturation of nitrogen. Once the metastable limit is reached, bubble nucleation occurs, triggering rapid bubble formation. Transient bright structures observed in Titan's lakes by the Cassini RADAR, known as "Magic Islands, " may in fact be bubbles within the liquid column. Bubbles can also form in rivers as they flow into lakes and seas, potentially influencing geologic structures, such as the delta seen in one of Titan's largest lakes, Ontario Lacus. Key Points: Nitrogen bubbles were created in the laboratory under Titan surface conditions Liquid methane and ethane must be present for bubbles to form (40–95 mol% methane‐alkane ratio) Identified two mechanisms for bubble formation: ethane titration (>86 K) and temperature‐induced stratification (<86 K)